Neurobrucellosis: Brief Review. Issue 6 (4th November 2021) - Bouferraa, Youssef; Bou Zerdan, Maroun; Hamouche, Ramzi; Azar, Eid; Afif, Claude; Jabbour, Rosette
Abstract : Background: Brucella are small, nonmotile, intracellular, and aerobic gram-negative bacteria. Of the 10 species that currently form the genus Brucella, 5 were shown to be pathogenic in humans. Review Summary: The epidemiology, clinical manifestations, diagnosis and imaging, and treatment of neurobrucellosis will be reviewed. Brucellosis's transmission to humans occurs by direct contact with contaminated animals. Older patients are at increased risk of nervous system involvement in brucellosis. Brucella spp. can lead to central nervous system involvement through direct damage via invasion of neural tissue or indirect damage caused by endotoxins or immune inflammatory reactions elicited by the presence of the bacteria in the body. Patients can have general nonspecific symptoms in addition to neurological and psychiatric symptoms. There are 4 diagnostic criteria for the diagnosis of neurobrucellosis, which include signs and symptoms suggestive of neurobrucellosis, a positive finding of Brucella spp. in the cerebrospinal fluid (CSF), and/or a positive titer of antibodies targeting brucella in the CSF, lymphocytosis with high protein levels and low glucose levels in CSF, and imaging findings (either cranial magnetic resonance imaging or computed tomography) peculiar to neurobrucellosis. For the treatment, a combined therapy is favored over monotherapy for the eradication of Brucella. Moreover, a multirouted therapy has been associated with increased treatment efficacy. The prognosis of neurobrucellosis is dependent on patients' clinical presentation: brucellar meningitis is associated with a good prognosis, whereas diffuse central nervous system involvement is associated with the development of long-term sequelae. Conclusions: Neurobrucellosis affects patients globally and in endemic areas. Neurologists should familiarize themselves with its clinical presentation, diagnosis, and treatment to provide optimal care for their patients.